Robot Emotion and Performance Regulation Based on HMM. (12th March 2013) - Xin, Liu; Lun, Xie; Zhi-liang, Wang; Dong-mei, Fu
This paper discusses the transference process of emotional states driven by psychological energy in the active field state space and also builds a robot expression model based on the Hidden Marov Models(HMM). Facial expressions and behaviours are two important channels for human-robot interaction. Robot performance based on a static emotional state cannot vividly display dynamic and complex emotional transference. Building a real-time emotional interactive model is a critical part of robot expression. First, the attenuating emotional state space is defined and the state transfer probability is acquired. Secondly, the emotional expression model based on the HMM is proposed and the performance transference probability is calculated. Finally, this model is verified by a 15 degrees of freedom robot platform. Moreover, the interactive effects are analysed by a statistical algorithm. The experimental results demonstrate that the emotional expression model can acquire an expressive performance and remove the mechanized interactive mode when compared to traditional algorithms.